Combined transcriptomics and metabolomics to reveal the effects of copper exposure on the liver of rainbow trout(Oncorhynchus mykiss) - Junhao Lu; Jinqiang Quan; Jing Zhou; Zhe Liu; Jieping Ding; Tingting Shang; Guiyan Zhao; Lanlan Li; Yingcan Zhao; Xiangru Li; Jiajun Wu (Ecotoxicology and Environmental Safety)
Copper (Cu) is recognized as an essential trace elements for the body; However, excessive levels of Cu can lead to toxic effects. We investigated the effects of Cu2+(75 μg/L, 150 μg/L, and 300 μg/L) on the rainbow trout liver. Combination of transcriptome and metabolome analyses, the regulatory mechanisms of the liver under Cu stress were elucidated. The results showed that Cu affected the antioxidant levels, leading to disruptions in the normal tissue structure of the liver. Combined transcriptome and metabolome analyses revealed significant enrichment of the insulin signaling pathway and the adipocytokine signaling pathway. Additionally, Cu2+ stress altered the amino acid metabolism in rainbow trout by reducing serine and arginine levels while increasing proline content. Apoptosis is inhibited and autophagy and lipid metabolism are suppressed; In summary, Cu2+ stress affects energy and lipid metabolism, and the reduction of serine and arginine represents a decrease in the antioxidant capacity, whereas the increase in proline and the promotion of apoptosis potentially serving as crucial strategies for Cu2+ resistance in rainbow trout. These findings provided insights into the regulatory mechanisms of rainbow trout under Cu2+ stress and informed the prevention of heavy metal pollution and the selection of biomarkers under Cu pollution.